Surabaya Dialect in Animation: Digital Communication Strategies for Preserving Local Culture - Nur Fauziah; Fauris Zuhri; Abdur Rosyid; Diana Budi Darma; Fithriyah Inda Nur Abida (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2024)
This study analyzes the use of digital communication strategies in animated films as a significant step toward sustaining the Surabaya dialect, Boso Suroboyoan. It focuses on three main aspects: (1) how animated films portray Boso Suroboyoan, (2) how visual elements in animation reflect cultural values, and (3) how animated films serve as an effective tool for preserving the local language and culture of Boso Suroboyoan. A case study approach was applied, examining animated films that feature Boso Suroboyoan as the primary language and emphasize Surabaya's cultural content. Data collection and analysis were conducted through content analysis, interviews, and public opinion surveys. The findings indicate that animated films using Boso Suroboyoan effectively convey cultural messages in an engaging and educational way. The vocabulary in Jowo Suroboyoan dialogues not only introduces regional language lexicon but also embodies the outspoken, assertive, and spirited character of the Surabaya people. Symbolism and visual elements in animation convey cultural values through narratives, settings, and 3D techniques. The strategic application of digital communication in dialogue and storylines successfully introduces and fosters pride in Surabaya's cultural heritage.